Knowledge, attitude and practice of contraception by female junior secondary school students in an urban community of Oyo-state, South west, Nigeria - Idowu, Ajibola; Aremu, Olatayo A.; Fehintola, Funmito O.; Popoola, Gbenga O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unintended pregnancies resulting in several maternal morbidities and mortalities are still a major public health challenge in most parts of the world. Female secondary school students are particularly vulnerable due to their engagement in unsafe sex and low uptake of family planning services. The study assessed respondents’ level of knowledge on, attitude to and practice of family planning. Methods: A cross-sectional study was conducted among 240 consenting female junior secondary school students in two public schools in Ogbomoso, South West Nigeria. Multi-stage sampling method was employed in recruiting the study participants and facilitated self-administered semi-structured questionnaire used for data collection. Descriptive statistics was done and Chi-square test used to compare categorical variables. The level of statistical significance was set at p <0.05. Results: The mean age of the respondents was 13.6±2.3 and 69.5% of them were early adolescents (10-13years of age). Almost all (92.3%) of the respondents were aware of family planning but only 58.1% and 55.3% of them had good knowledge on and positive attitudes towards family planning respectively. In all, 64.0% of the sexually active respondents had ever used family planning. Condom was the commonest family planning method ever used; reported by 65.0% of those who had ever used family planning. Fear of side effects was the main reason among non-users. Conclusions: Family planning uptake among sexually active female students is low in Southwest Nigeria. There is urgent need for aggressive awareness campaigns to improve the knowledge score and attitude of students to family planning in Nigeria.